KORBAN DAN PELAKU KEKERASAN FISIK DALAM RUMAH TANGGADI KOTA PEKANBARU - Ermailis Ermailis (JIP ( Jurnal Industri dan Perkotaan ), 2011)
this paper aim to know the violence factor in the family. In general, victims ofdomestic violenceis awife, while theperpetrators ofviolencearehusbands. Why domenoften become violence? Physicallymenare stronger than women and has invest edinits growth habittousephysical force, other than thatwomenare often economically depen denton her husband